The Impact of Human Resource Development and Motivation on the Performance of Harvesters at PT. Cinta Raja - Abraham Eryo Panjaitan; Marzuti Isra (Jurnal Ragam Pengabdian, 2026)
Human resources are a key element in the establishment and structuring of an organization within a company. To manage activities relating to human resources, it is essential to foster motivation amongst the company’s employees. The higher the quality of human resources, the better the performance of employees will be, and the better the outcomes in terms of productivity and strategic efficiency will be. This research was conducted at PT. Cinta Raja, Serdang Bedagai Regency, North Sumatra Province. The research was carried out from February to April 2026. The results of the study revealed that the human resource development programme and employee work motivation implemented at PT. Cinta Raja were of a significant standard and achieved their objectives more effectively. Furthermore, motivational training activities were maintained to uphold quality and quantity within the company, thereby ensuring that the provision of motivational rewards to employees for better performance had been achieved in line with the objectives set by PT. Cinta Raja.